Teori Ketepatan Waktu Hukum Terhadap Relaas Pemanggilan Melalui e-Summons dan Surat Tercatatḋocx - Pakpahan, Novritsar Hasintongan (Fakultas Hukum Universitas Primagraha, 2023)
Serve has been considered as an essential act of court practice to realize legal rights and legal obligations of parties involved. The failure in serving properly and rightfully would result in violation of legal rights. Serve has been advanced through modern methods such as e-Summons and registered mailing. However, there has not been proper regulation regarding serving through e-Summons and registered mailing method. Therefore, there should be deployed legal punctuality theory to analyze problem of the proper time serving and the legal framework for time serving through conventional means, e-Summons, and registered mailing. This research is urgent to be conducted because of legal certainty in serving through e-Summons and registered mailing. The applied research methods are statute approach, conceptual approach. The research discussed the result as finding there should be legal authority for panel of judges in deciding the day of the trial to determine proper time serving with the advice of bailiff who knows the location of related parties and such regulation should be regulated in form of act instead of supreme court regulation to ensure law uniformity